High-Chondrocyte-Viability Osteochondral Allograft Transplantation in the Knee for Revision of Failed Cartilage Repair Procedures - DeFroda, Steven F.; Moore, Julian M.; Rucinski, Kylee; Stannard, James P.; Nuelle, Clayton W.; Cook, James L. (The Journal of Knee Surgery, 2025)
Revision osteochondral allograft transplantation (OCAT) has historically yielded inferior outcomes compared with primary procedures. This study evaluates outcomes following revision OCAT using high-chondrocyte-viability (HCV) OCAs for functional graft survival. A prospective registry was analyzed for HCV OCAT outcomes. Patients were grouped into primary (n = 182) or revision (n = 70) OCAT cohorts. Demographic, surgical, and follow-up data were collected. Revision cases were further subclassified based on prior cartilage procedures (marrow stimulation, osteochondral, or cell-matrix-based). Functional graft survival and validated patient-reported outcomes were assessed at a mean follow-up of 43 months. At final follow-up (FFU), functional graft survival was 79.1% for primary and 71.4% for revision OCAT. Overall survival at > 2-year follow-up was 84% (primary) and 80% (revision). Patients with failed revision OCAT reported significantly lower Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function scores at 1-year (mean: 40.8, p = 0.026). Bipolar tibiofemoral revisions conferred increased failure rates (odds ratio: 3.86, p = 0.033). Cell-matrix-based revision cases had significantly higher graft survival (100%) compared with osteochondral revisions (58.6%, p = 0.049). Satisfaction with revision OCAT was high (75.0%), and 84.1% would undergo the procedure again. With evidence-based patient selection, individuals who have failed previous cartilage defect surgical treatments and meet the indication criteria are likely to benefit from revision OCAT with HCV allografts. Optimal candidates for revision OCAT in the knee are patients with a history of marrow stimulation or cell-based matrix procedures who have limited comorbidities, do not require tibiofemoral bipolar OCAT, and strictly adhere to postoperative restriction and rehabilitation protocols.
Keywords: osteochondral allograft transplantation; cartilage repair; revision surgery; chondrocyte viability